The Influence of Job Satisfaction and Work Motivation on the Performance of Employees at Service Bureau Princess Bandar Lampung - Nadila, Dea; M. Oktaviannur (International Journal of Economics (IJEC), 2025)
Service bureau Princess is a company operating in the service sector, which offers vehicle administration services such as driving courses, making driver's licenses and tax payments located in Bandar Lampung. Service bureau Princess in running its business experiences challenges such as experiencing instability in employee performance appraisals and employee absenteeism which can be influenced by job satisfaction and work motivation in employees of Service bureau Princess Bandar Lampung. This analysis intends to examine the impact of job satisfaction and work motivation on employee performance in Bandar Lampung. This analysis utilizes primary data collected through questionnaires and then analyzed using SPSS software version 27. This research applies a quantitative approach Employing multiple linear regression models. Sampling in this study was carried out using the census techpnique by taking the entire population into the participants in this research, namely all employees of Service bureau Princess Bandar Lampung. Based on the results of the R-squared value test, with an R Square value of 0.574, which signifies that the job satisfaction and work motivation variables affect the employee performance variable by 57.4% as well as the others 42.6% is influenced by external aspects in this analysis.